An investigation of alternative bean seed marketing channels in Uganda - David, S.; Kasozi, S; Wortmann, Charles S. (International Center for Tropical Agriculture, 1997)
The distribution of newly released bean seed is often a weak link in the technology transfer process. To assist national commodity programs to devise cost-effective delivery systems, research was conducted in Uganda to test the appropriateness of bean seed distribution through four non-conventional channels: rural shops, a rural health clinic, women`s groups and an NGO. The findings confirm the feasibility of distributing seed packets through market and non-market channels and show that each delivery system has advantages and disadvantages which must be assessed by seed suppliers in a country-specific context. The paper offers guidelines for the distribution of new bean varieties by formal institutions